Prayer Movement Material and Its Effect on PAI Learning Outcomes (Case Study at SMP Negeri 2 Simeulue Timur) - Adi Saleh; A’zizah A’zizah; Wolly Mistiar; Evi Mulyama (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The competency base of Islamic subjects developed at SMPN 2 Simeulue Timur is directed at the growth of faith and piety to Allah SWT, mastery of academic abilities, arts and complete personality development. This research includes the type of quantitative research, In accordance with the type of research, this research uses a quantitative approach. The data analysis technique used is the analysis of "Product Moment." Based on the results of the calculation of the product moment correlation rxy = 0.824. After consulting with the product moment rtable at a significance level of 5% with N 30, it was obtained that rtable = 0, 361 while at the 1% significance level, the value of rtable = 0.463 looks at the results of the presentation of the data above, it can be said that rxy (calculated) is greater than rt(r table) both at the 5% and 1% significance level if described, then rt 0361 < 0824 > 0.463. Thus, the hypothesis which reads that there is a relationship between Islamic learning achievement and the practice of praying for students at SMPN 2 Simeulue Timur, can be accepted. Thus the working hypothesis proposed is proven, because the results of the study prove that there is a positive and significant correlation between fiqh learning achievement and students' prayer practice. 463 Seeing the results of the presentation of the data above, it can be said that the rxy (calculated) is greater than the rt (r table) both at the 5% and 1% significance level if described, then rt 0361 < 0824 > 0.463. Thus, the hypothesis which reads that there is a relationship between Islamic learning achievement and the practice of praying for students at SMPN 2 Simeulue Timur, can be accepted.